Emergency department performance evaluation by an integrated simulation and interval type-2 fuzzy MCDM-based scenario analysis - Gul, Muhammet; Celik, Erkan; Gumus, Alev Taskin; Guneri, Ali Fuat (INDERSCIENCE ENTERPRISES LTD, 2016)
Emergency departments (EDs) have an important position in healthcare system environment because of their serviceability to the patients with several illnesses and injuries at all hours of the day and night. Therefore, efficient management of these departments by executives and service providers is only possible with effective tools such as simulation. The concept of multiple criteria decision-making (MCDM) is applicable by computer simulation for decision analysis and performance evaluation of an ED. This study proposes an integration of computer simulation, MCDM methods of interval type-2 fuzzy analytic hierarchy process (IT2FAHP), and ELECTRE for an ED system in a university hospital. Due to the high uncertainty in ED operations, interval type-2 fuzzy sets (IT2FSs) are used in MCDM process. Consequently, the integrated method can be used as a useful tool to evaluate the ED performance and select the best scenario considering different numbers of nurses and doctors for three shifts.
Keywords: emergency department; computer simulation; multiple criteria decision-making; MCDM; interval type-2 fuzzy sets; IT2FSs; COMPUTER-SIMULATION; CUSTOMER SATISFACTION; DECISION-MAKING; SYSTEM; CARE; DEA; Engineering; Operations Research & Management Science